(untitled) (Tanzania Medical Journal, 2009)
Objective: The objective of this study was to investigate the possible reasons for decreased anti- inflammatory and analgesic activities in patients using generic diclofenac sodium tablet formulations (50mg) in Dar es Salaam. Methodology: Different diclofenac sodium tablet products from different manufacturers were collected from twelve wholesale pharmacies with good storage conditions. In total 80 samples were collected, with a minimum of five samples from each wholesale pharmacy. In addition a survey on brands available and the pricing of different diclofenac formulations in 120 retail pharmacies was conducted. Analyses of the sampled tablet formulations were performed at the laboratory of Tanzania Food and Drug Athority. Both validated British and United States Pharmacopoeia methods were used to perform the analyses. Results: On visual appearance of tablets, 18% of the collected samples had cracks and white patches on the coat. Same number of samples could not meet the requirements for drug content and disintegration rates respectively, whereas, 27 % failed the dissolution rate tests. Voltaren® (Norvatis Pharma, Switzerland), the originator's product was the most expensive, less available and a less bought product. Vivian® (Lincoln Pharma, India) and Dyclomax® (Medreich Laboratories, India) were sold cheapest and were available in all pharmacies including those in the peripheral part of the city. Conclusion: Low anti- inflammatory and analgesic response reported by many patients with different pain conditions could be associated with the use of poor quality diclofenac sodium. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 20-23